Uchwały zarządu i rady nadzorczej spółki akcyjnej w procedurze podwyższenia kapitału zakładowego w granicach kapitału docelowego - Saczywko, Maksymilian (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The paper focuses on resolutions adopted by the management board and the supervisory board of a joint-stock company to increase the share capital of a public limited company within its authorised capital. The author outlines the origin and nature of the authorised capital, the content and form of the abovementioned resolutions, their legal nature and different types of possible defects in them. Challenging defective resolutions is particularly important in practice. That matter is not regulated explicitly in Polish law. The possible solutions available under Italian and Spanish regulations that are presented indicate that the challenging of defective resolutions of the management board and the supervisory board in capital commercial companies, particularly those adopted in connection with authorised capital, should also be regulated in Poland.